2012
DOI: 10.1042/an20120015
|View full text |Cite
|
Sign up to set email alerts
|

Di-(2-Ethylhexyl) Phthalate and Autism Spectrum Disorders

Abstract: ASDs (autism spectrum disorders) are a complex group of neurodevelopment disorders, still poorly understood, steadily rising in frequency and treatment refractory. Extensive research has been so far unable to explain the aetiology of this condition, whereas a growing body of evidence suggests the involvement of environmental factors. Phthalates, given their extensive use and their persistence, are ubiquitous environmental contaminants. They are EDs (endocrine disruptors) suspected to interfere with neurodevelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 42 publications
2
81
1
2
Order By: Relevance
“…In a cross-sectional study, Kim et al (2009) reported an inverse association between childhood MEHP and MEOP and teacher-rated ADHD scores and thus more ADHD symptoms. Using a case-control design, Testa et al (2012) found a positive association between prenatal MEHP and autism spectrum disorder diagnosis.…”
Section: High Molecular Weight Phthalatesmentioning
confidence: 97%
See 1 more Smart Citation
“…In a cross-sectional study, Kim et al (2009) reported an inverse association between childhood MEHP and MEOP and teacher-rated ADHD scores and thus more ADHD symptoms. Using a case-control design, Testa et al (2012) found a positive association between prenatal MEHP and autism spectrum disorder diagnosis.…”
Section: High Molecular Weight Phthalatesmentioning
confidence: 97%
“…However, selection bias is only problematic if it is dependent on both exposure and outcome (Oleckno 2008), and thus the possibility of bias is minor. One of the eleven studies was a case-control study (Testa et al, 2012); therefore, selection of a representative control group is essential to ensure internal validity (Oleckno, 2008). Testa et al used 45 randomly selected age-and gender-comparable outpatients as their control group, and thus, the possibility of selection bias is minimized.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…Higher urinary concentrations in autistic children [105]. Decreased Diethylhexyl Phthalate glucuronidation in autistic children [106].…”
Section: Diethyl Phthalate and Dibutylphthalatementioning
confidence: 99%
“…Environmental contaminants like arsenic and DEHP have been implicated in some neuropathological conditions (Testa et al, 2012;Siniscalco et al, 2013;Akyuzlu et al, 2014;Manivannan et al, 2015). There are also growing concerns about the adverse effects of toxicants on neurodevelopment (Kim et al, 2009;XiuJuan et al, 2013).…”
Section: +mentioning
confidence: 99%